2021
DOI: 10.1259/bjr.20210907
|View full text |Cite
|
Sign up to set email alerts
|

The Wavelia Microwave Breast Imaging system–tumour discriminating features and their clinical usefulness

Abstract: Objective: The Wavelia Microwave Breast Imaging (MBI) system, based on non-ionising imaging technology, has demonstrated exciting potential in the detection and localisation of breast pathology in symptomatic patients. In this study, the ability of the system to accurately estimate the size and likelihood of malignancy of breast lesions is detailed, and its clinical usefulness determined. Methods: Institutional review board and Health Products Regulatory Authority (HPRA) approval were obtained. Patients were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…A total of 92% of patients say they recommend this test method. The inspection time is as long as 50 min [ 20 , 21 , 22 ]. A Quadratic Discriminant Analysis (QDA) classifier was trained in a 3D feature space to discriminate malignant from benign lesions.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 92% of patients say they recommend this test method. The inspection time is as long as 50 min [ 20 , 21 , 22 ]. A Quadratic Discriminant Analysis (QDA) classifier was trained in a 3D feature space to discriminate malignant from benign lesions.…”
Section: Discussionmentioning
confidence: 99%
“…For specificity, it was found in [1] that the specificity (true negative rate) for the Mammowave system was approximately 62% ( 32 /52 correctly identified as negative). Additionally, in [51], the results from the same Wavelia clinical study as [7] were further analyzed using Quadratic Discriminant Analysis (QDA) to differentiate benign and malignant lesions. Accurate discrimination was achieved in 88.5% cases, and accurate lesion size estimate in 76.5% of cases.…”
Section: A Sensitivity and Specificity Of Microwave Imaging Systemsmentioning
confidence: 99%
“…In this FiH study, Wavelia demonstrated the capacity to detect and approximate underlying breast abnormalities to the appropriate location, in patients with palpable biopsy-confirmed invasive carcinomas and benign breast lesions, such as cysts and fibroadenomas [12]. The device also demonstrated promising results in delineating the size and malignancy risk of the detected breast lesions [14].…”
Section: Introductionmentioning
confidence: 96%
“…During the FiH clinical investigation, the Wavelia MBI system showed promise for measuring lesion size with a more favorable linear trend between MBI and postsurgery histological lesion size, compared to the results obtained for conventional imaging [14]. Two challenging patient cases in terms of breast lesion sizing are indicatively discussed in Results Section 3.2, to better highlight the status of the MBI lesion sizing method, as integrated into the current version of the Wavelia QIF.…”
mentioning
confidence: 99%